ANALISIS PENDAPATAN KELOMPOK USAHA BERSAMA PERIKANAN TANGKAP DI DESA HANDIL TERUSAN KECAMATAN ANGGANA - Harry Sanjaya; Nurul Ovia Oktawati; Oon Darmansyah (2339-1324, 2023)
The purpose of this study was to analyze the value of profits and efficiency of the Joint Capture Fisheries Business Group in Handil Terusan Village. This research was conducted in June 2021 – June 2022 in Handil Terusan Village, Anggana District, Kutai Kartanegara Regency. The data collection method used is a case study, which is a detailed study of a research subject. The sampling method used is purposive sampling with the number of respondents as many as 30 people. The data obtained were analyzed using a descriptive qualitative-quantitative method with a focus on the method of analyzing the value of profits and efficiency of the Joint Capture Fisheries Business Group. The benefit of using gill nets is Rp. 52,615,675 per month with an average profit of Rp. 2,287,638 per month. The advantage of using skeleton fishing gear is Rp. 25,645,571 per month with an average profit of Rp. 5,130,914 per month. The advantage of using fishing gear is Rp. 8,274,028 per month with an average profit of 4,137,014 per month. The results of the profit and efficiency analysis show that the Joint Capture Fisheries Group can be said to be profitable and efficient to continue, as evidenced by the average R/C ratio for gill net fishing gear of 2.8, for skeleton fishing gear of 2 ,5, and for fishing gear it is 2,9. The value of R/C ratio > 1 means that for gill nets it is 2.8 times larger, for skeletons it is 2.5 times larger, and for fishing rods it is 2.9 times larger. Key Words : Profit and Efficiency of Joint Capture Fisheries Group, Handil Terusan Village